Stemness and angiogenic gene expression changes of serial-passage human amnion mesenchymal cells - Fatimah S.S.; Tan G.C.; Chua K.; Tan A.E.; Hayati A.R.; Nur Fariha Mohd Manzor (2024)
Indexed by SCOPUS/WOS